Analisis Multi-Aspek terhadap Implikasi Penambangan Pasir Darat di Kabupaten Bintan - Rizky Octa Putri Charin; Khairi Rahmi (Society, 2024)
This research examines the various implications of land-based sand mining activities in Bintan Regency, which have been ongoing since the 1980s. These activities are closely associated with significant environmental impacts resulting from mining processes that alter the landscape, causing changes to the physical, chemical, and biological environment. One notable outcome is the creation of the Telaga Biru Desert in Bintan Regency, which has become a popular natural tourist destination since 2015. The reutilization of post-mining areas after years of abandonment raises a critical question: How does the government address the multi-dimensional implications of land sand mining? These impacts encompass both positive outcomes, such as economic opportunities, and negative consequences, including risks to the physical and non-physical environment, as well as socio-economic challenges. This study adopts a descriptive and qualitative approach, utilizing primary and secondary data collection, processing, and analysis. The findings reveal that land-based sand mining activities in Bintan Regency have led to significant environmental and socio-economic consequences, including landscape alterations, biodiversity loss, and water pollution. Economically, the transformation of Telaga Biru Desert into a tourist destination highlights the potential for alternative uses of post-mining areas. However, the findings underscore the urgent need for clear governance frameworks to balance economic development with environmental sustainability.